Conocimiento y uso de ácido fólico periconcepcional. Estudio comparativo entre puérperas adolescentes y adultas en Santiago de Chile - Lay-Son R., Guillermo; Pardo V., Rosa Andrea; Tenhamm T., Tamara; Recabal G., Pedro; Rebolledo D., Cristian; Parra, Jorge; Ojeda M., Natalia; Navarrete C., María Francisca; Muñoz B., Pilar; Muñoz K., María José; Espina M, Pablo; Dib M., Martín; et al. (Revista Hospital Clínico Universidad de Chile, 2007)
Introduction: intake of Folic Acid (FA) before conception and during early pregnancy reduces the incidence of neural tube defects (NTD). In Chile the management of the pregnant adolescent women is a relevant public health problem. So, the aim of this study was to determine the level of knowledge and intake of FA in a sample of adolescent and older parturient. Methods: a survey was conducted in one group of teenagers (group A) and another group of older puerperal (group B) corresponding to four public maternities of Santiago. Results: finally, 79 teenagers and 263 older women were surveyed. Both groups showed a poor knowledge about the benefit of intake of FA during this period. Regarding the control before pregnancy, we found an attendance of 10.1% in the group A and 24.7% in the group B, whereas only 5.1% of the group A and 1.9% of the group B had an intake of FA according to the medical recommendation. Conclusion: our patients have scanty information about the benefits of the periconceptional intake of FA. It seems necessary to design new methods and tools in order to increase the use of the FA in women of childbearing age, especially in the groups at risk for NTD.